2004
DOI: 10.1080/00140130410001686357
|View full text |Cite
|
Sign up to set email alerts
|

A 16-year follow-up study of physical capacity in relation to perceived workload among ageing employees

Abstract: The main purpose of this study was to ascertain musculoskeletal and cardiovascular capacity among ageing employees in relation to workload over a period of 16 years. The data were obtained by physical capacity tests and ratings of perceived exertion (RPE) during working day. The study group consisted of 89 subjects, who were all employed in the municipal branch and were on average 51.9 years old at the beginning of the follow-up period in 1981 and 67.3 years in 1997, when the most of the subjects had retired (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 20 publications
4
54
1
2
Order By: Relevance
“…Existing evidence is limited by methodological problems due to categorization and misclassification of physical activity at work and during leisure-time, and also activity related to transportation and household work. Earlier studies have shown ambiguous results: LTPA was beneficial to HGS among middle-aged men (25) whereas no association was seen between baseline physical activity or persistent physical activity and HGS in midlife in a recent follow-up study (16). Interaction between physical exposures at work and physical activity during leisure-time is a possible bias, but we found no interaction between exposures and LTPA except in one exposure group among men.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Existing evidence is limited by methodological problems due to categorization and misclassification of physical activity at work and during leisure-time, and also activity related to transportation and household work. Earlier studies have shown ambiguous results: LTPA was beneficial to HGS among middle-aged men (25) whereas no association was seen between baseline physical activity or persistent physical activity and HGS in midlife in a recent follow-up study (16). Interaction between physical exposures at work and physical activity during leisure-time is a possible bias, but we found no interaction between exposures and LTPA except in one exposure group among men.…”
Section: Discussioncontrasting
confidence: 87%
“…A few longitudinal studies have had contradictory results. Savinainen et al (15) found no association between perceived physical workload at baseline and HGS after 22 years of follow-up (mean age 67.3 at follow-up); while Stenholm et al (16) found that self-reports of physical work at baseline were associated with lower HGS at follow-up 22 years later (mean age 48 at follow-up). However, changes in exposure or total amount of exposure during the follow-up period were not taken into account in these studies.…”
Section: Physical Exposures At Work Affecting Midlife Hand-grip Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies have indicated that physically demanding working conditions, such as repetitive monotonous work or lifting (8)(9)(10)(11)(12), and psychosocially demanding working conditions, such as low job control or high job demands (13)(14)(15)(16), are associated with poorer physical functioning among midlife and older employees. However, evidence on the health effects of changes in these working conditions is insufficient, especially for physical working conditions.…”
mentioning
confidence: 99%
“…Flere studier har vist at varigheden af de fysiske påvirkninger har betydning for udvikling af kroniske bevaegeapparatsproblemer og nedsat funktionsevne (Leino-Arjas, Solovieva, Riihimaki, Kirjonen & Telama, 2004;Savinainen, Nygard & Ilmarinen, 2004). De Zwart et al anfører, at årsagen til, at fysiske påvirkninger i arbejdet kan få laengerevarende indvirkning på den fysiske funktionsevne, er en proces hvor akutte forandringer kan udvikle sig til kroniske forandringer, hvis der ikke er den nødvendige tid til restitution (de Zwart, Frings-Dresen & van Dijk, 1995).…”
unclassified